Optimisation of emulsified liquid culture system for bacterial poly-3-hydroxyalkanoate production / Aishat Abdulwaheed - Aishat , Abdulwaheed (2024)
The use of polyhydroxyalkanoates (PHAs) as a polymer in various industries, including packaging and medicine, is receiving significant attention due to their biodegradability and biocompatibility. However, the high cost of production from carbon sources remains a major obstacle to the widespread use of PHAs as alternative polymers. Consequently, there has been a search for cost-effective substrates that can yield high productivity. One such substrate is cooking oil, which serves as an energy and carbon source. However, using an immiscible substrate like oil presents unique challenges because the fermentation liquid consists of a heterogeneous multiphase system that makes it difficult for bacterial to grow. Therefore, this study aimed to optimize the PHA production using the Box-Behnken method with oil, inoculums, and surfactants as the variables. The amount of PHA produced was comparable to the control experiments using a pure, single-type fatty acid as the sole carbon and energy substrate. The addition of surfactant (Tween-80) to the mixture of liquid medium and oil facilitated the emulsification of the immiscible substrates, thereby promoting bacterial growth. The optimal conditions for PHA production were determined as follows: biomass of 0.375 ml, oil of 1.25 g, and surfactant of 0.125 ml per 100 ml of medium. Furthermore, the molecular weight and chemical characteristics of the extracted PHA were analyzed. The study demonstrated the effectiveness of surfactants in achieving favourable cellular growth while simultaneously enhancing PHA production.